The impact of oral isotretinoin on ovarian functions of acne patients complaining of polycystic ovarian syndrome: a prospective study - Heba I. Elnagar; Osama A. Hashem; Hany O. Aboelwafa; Ehab Elhelw; Mohamed L. Elsaie (Journal of Ovarian Research, 2024)
Abstract Background Women have polycystic ovarian syndrome (PCOS) at higher rates than any other endocrine condition with an average incidence rate of 6 to 8%. Acne is an immune mediate common condition frequently affecting adolescents and adults and is often associated with PCOS. The objective of the study was to assess the impact of oral isotretinoin on ovarian functions of acne patients suffering from PCOS. Forty women with a clinical diagnosis of acne as well as PCOS participated in this prospective clinical trial. Participants were given oral doses of isotretinoin ranging from 0.5 to 1 milligram per kilogram (mg/kg), for a total of 120 to 150 mg/kg. To establish baseline values of hormone levels, on days 2–5 of the menstrual cycle, venous blood samples were obtained. Moreover, global acne grading system (GAGS), follicle count, and bilateral ovarian volumes were evaluated both before and after isotretinoin treatment. Results A significant reduction in global acne score from pre-treatment levels to post-treatment levels was observed (11.58 ± 5.857 vs. 1.65 ± 1.369). Ovarian volume was significantly reduced from 10.26 ± 1.539 before treatment to 8.74 ± 1.436 after treatment on the right side (P < 0.001) and from 11.08 ± 1.564 before treatment to 9.36 ± 1.479 after treatment on the left side (P < 0.001). A significant reduction in free testosterone level and hirsutism scores were observed after treatment (P < 0.001; P < 0.01 respectively. Conclusion Isotretinoin may exert beneficial effects in hyperandrogenic women with PCOS and needs to be further evaluated by large multicentre controlled trials.